PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA CAFE DEUMDEE RANGKASBITUNG - Rina Martiana; Sheli Apriani (Universitas La Tansa Mashiro, 2019)
Indonesian people today in fulfilling their food needs, they prefer to consume culinary snacks or fast food. One of today's rapidly growing businesses and experiencing the tight competition is the culinary business. This increasingly strong competition makes a lot of culinary field businesses that produce products of the same type but with a variety of services. The culinary industry is growing in Indonesia. From the Creative Economic Agency (BEKRAF) data, creative economic contributions to gross domestic product (GDP) are always increasing. The purpose of this research is to know the effect of product quality and service quality to customer satisfaction at Cafe Deumdee Rangkasbitung.The research method used is descriptive method using a quantitative approach, i.e. to explain a problem based on the data in the form of figures (statistical data). The population used in this research are the consumers who pay a visit to Deumdee with a total of 17.993 Cafe visitors, using the formula error level slovin 10% then the samples obtained as many as 99 consumer. The technique of data collection is the observation, study of librarianship and the questionnaire. Data analysis technique used is multiple regression analysis, correlation analysis, multiple coefficient of determination, t-test and f-test.Based on the research conducted, t test results obtained that the quality of the product (X 1), namely the significant level of significant extent < (0.017 < 0.05). So starting in H0 and Ha acquired significant value received and the quality of service (X 2), namely the significant level of significant extent < (0.043 < 0.05). So starting in H0 and Ha is received. That means there is the influence between product quality against consumer satisfaction at Cafe Deumdee and there are Influences between the quality of service of consumer satisfaction on a Cafe Deumdee. As well as the results of hypothesis testing the F value obtained significant i.e. 0.000 value smaller than 0.05 significant level. Or F-count is greater than the F-table (0.27705 > 0, 309). Then it can be concluded that the quality of product and service quality to customer satisfaction simultaneously.